PROSPECTS FOR THE DEVELOPMENT OF INNOVATIVE ACTIVITIES OF COMMERCIAL BANKS (American Journal of Business Management, Economics and Banking, 2024)
In this thesis, the objectives of the theoretical analysis of the monetary circulation, credit system and banks in the national economy, the liabilities of the government, commercial banks, and other national institutions are used as money. The majority of monetary operations are carried out without cash, through checks and financial assets equivalent to them.